Disease free seed potato production through seed plot tech nique at farmers’ level in Bangladesh (The Journal of Plant Protection Sciences, 2023)
Among the reasons for the low yield of potato  in Bangladesh, lack of disease free quality  seed tubers, lack of improved varieties/ practices and disease problems are noticeable  (4). The total seed potato requirement of  Bangladesh is estimated at about 7.50 lakh  tons per annum. Locally produced certified  seed meets about 6% of the total requirement  (10). Every year about 10,000 tons of potato  seeds are being imported with a very high ex pense of foreign currency. Farmers, traders or  cold storage owners supply the remaining  seed. The cost of good quality planting mate rials produced and sold by the Bangladesh  Agricultural Development Corporation  (BADC) and private farms are beyond the  reach of poor farmers. Therefore, the farmers  are forced to acquire poor quality seed from  the informal system. In the seed plot tech nique (SPT), disease free potato seed tuber  (whole tuber), early planting, maintaining iso lation distance by planning non host (wheat)  surrounding the seed plot, use of HYV disease  resistant varieties, roughing diseased plant at  30-45 days after planting (DAP), spraying insecticide (Admire) for vector control, spray ing fungicides to minimize fungal diseases,  weeding, other improve management, haulm  pulling at 80DAP, harvesting, sorting, grad ing, seed treating with boric acid (3%) and  storing at cold store found most effective in  producing disease free seed potatoes at farm ers’ field at different locations (2). Efforts to  increase the quality of planting materials, pro duction techniques in the informal system will  help the resource poor farmers by making  available quality planting material, higher  yields and finally alleviate poverty. Hence,  farmers’ field trials was undertaken to im prove the informal seed system in potato seed  growing areas of Bangladesh, and to provide  farmers with an alternative source for quality  planting materials at a reasonable price.
Keywords: Farmers; Agricultural; potato